Implementasi Media Pembelajaran Pada Mata Pelajaran SKI dalam Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas X MA Darun Najah - Khoiriyah, Alfiatul; Waqfin, Mohammad Saat Ibnu (Universitas KH. A. Wahab Hasbullah, 2023)
ABSTRACT The process of pushing teaching materials or materials really needs media assistance to make it more attractive, efficient, practical, and effective in encouraging teaching materials and knowledge information, as well as having an appeal for students to pay attention to and understand the learning material presented. Given that this SKI subject is very important for students to know more clearly and in detail about the history and development of Islam in the past, it is necessary to choose good media such as audio-visual combined with image and audio rotation and followed by videos or films about the material. history so that students can be enthusiastic about learning also so that they can increase students' knowledge and insight. This study aims to find out how the implementation of learning models using learning media in the form of audio-visual in increasing motivation and learning outcomes of X MA Darun Najah Ngijo-Karangploso Malang students in SKI subjects. This qualitative-descriptive research was conducted following a research flow consisting of the stages of preparation, implementation, observation, and reflection. The research data was obtained using library and field study techniques, and was carried out continuously. This research proves that the use of learning media in the form of audio-visual can increase the learning motivation and learning of class X MA Darun Najah students, especially in SKI subjects. However, in practice there are some students who have not been able to achieve the learning target.